FEAR - Camerablu, Redazione (La camera blu. Rivista di studi di genere, 2012)
Fear – an emotion that we all experience in our life – may assume a variety of expressions. It occupies the intimate part of our being and may produce symptoms in our bodies; it may be manipulated for purposes of repression and social control. A frequent kind of this emotion is connected to the fear of losing or being abandoned by a loved one, a fear that we experience from the beginning of our life, when we are separated from our mother’s body. Fear is often connected with violence: there is the women’s fear for the recurrent gender violence, and the fear experienced on the battlefield by soldiers compelled to repress their emotions in order to play the part of the hero. This issue features studies, memories and educational projects dealing with the subject of fear. riflessioni teoriche, esperienze di ricerca, testimonianze, progetti di educazione e trasformazione nei quali questo sentimento, tanto profondo quanto difficile da definire, svolge un ruolo chiave. Fear – an emotion that we all experience in our life – may assume a variety of expressions. It occupies the intimate part of our being and may produce symptoms in our bodies; it may be manipulated for purposes of repression and social control. A frequent kind of this emotion is connected to the fear of losing or being abandoned by a loved one, a fear that we experience from the beginning of our life, when we are separated from our mother’s body. Fear is often connected with violence: there is the women’s fear for the recurrent gender violence, and the fear experienced on the battlefield by soldiers compelled to repress their emotions in order to play the part of the hero. This issue features studies, memories and educational projects dealing with the subject of fear.